Decision Support System for Teacher Performance Assessment Using Weighted Product Method with Web Application - Rachman Arief; Achmad Bagus Darmawan; Rayinda Aseti Prafianti (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2022)
This study aims to assess the performance of teachers in applying all competencies in the learning process, mentoring in school education and planning for continuous professional development for teachers. Where in the process of assessing teacher performance at the school, they still use manual applications with a simple addition method and the lack of speed in processing teacher performance assessments is increasing from year to year. To solve these problems, the Weighted Product method was chosen, this method helps teacher performance appraisal decisions so that they get the best results, then implements the method into an application decision support system to speed up the assessment process. Then the final result of this study with a calculation accuracy rate of 100% based on manual calculations and calculations on the application with the results agreeing to the decision support system made.